Precision RPS Calibration for the BICEP3 Telescope - Sjoberg, Kane (Zenodo, 2024)
Here we present the results of characterization and upgrades to the Rotating Polarized Source (RPS) for the BICEP3 Telescope, an advanced refracting telescope designed to measure the polarization of the Cosmic Microwave Background at 95GHz. Characterization of the behavior of the RPS in-lab is critical for developing empirical expectations of achievable angle uncertainty when deployed in the field. Sources of error in the field include wind, adverse weather conditions, and even thermal expansion due to sun exposure of the guy wires that anchor the RPS on its mast at the South Pole. With the installation of a new high-precision encoder system enhancing position measurement accuracy and quantifying mechanical error, we present new results about the quantitative behavior of the Rotating Polarized Source and detail improved characterization and control of the RPS’s behavior, towards the goal of complete repeatability and a decreased error budget from current by two orders of magnitude. Astro 98